Etika Hakim dalam Kehidupan Sehari-hari: Penggunaan Media Sosial oleh Hakim di Indonesia - Surbakti, Farrel Eden (UI Scholars Hub, 2022)
With the development of technology which is rapidly making the community easier in communicating and searching for information such as social media. Social media itself has different characteristics and types and has advantages and disadvantages. The use of social media does not look at a person's status such as age, gender, religion, or profession. At this time many judges use social media to communicate and search for information and interact with the community. Judges in carrying out their obligations as bearers of the legal profession are framed by an institutional institution that is formulated into a code of ethics for the professional profession of judges. Judges within the Supreme Court and lower judicial bodies are bound by the Code of Ethics and the Code of Conduct for Judges (KEPPH) as outlined in the Joint Decree of the Chief Justice and Chair of the Judicial Commission in 2009. Indonesian judges are not prohibited from using social media but the use of social media by judges can raise very important questions because the way judges use social media can influence people's trust in judges in court. In KEPPH there are no rules or ways for judges to use social media. So the judge is unconsciously still bound by KEPPH when using social media. At this time there are still judges who violate KEPPH in using social media. In various countries such as Canada, Rhode Island and UN organizations have made rules and ways for judges to use social media properly and correctly so as not to reduce the public's trust in judges. Therefore, this research was conducted aiming to help the Supreme Court and the Judicial Commission to be able to make regulations or guidelines against judges in using social media, as well as judges to be able to use social media properly and correctly